Comparative 'omic' profiling of industrial wine yeast strains - Rossouw, D. (Stellenbosch : Stellenbosch University, 2009)
Thesis (PhD(Agric) Viticulture and Oenology. Wine Biotechnology))--University of Stellenbosch, 2009.